An intelligent virtual environment to support cognitive rehabilitation: relearning meal preparation skills for independent living. (4th December 2009) - Fok, S.C.; Lim, S.Y.E.; Chan, G.Y.C.
The capability of virtual reality to create dynamic three-dimensional realistic environments, within which behavioural responses to stimulus can be assessed, offers many new opportunities in cognitive rehabilitation. To further advance the state-of-the-art in virtual rehabilitation environments, this paper a framework for an intelligent virtual cognitive rehabilitation environment and presents the development of a virtual kitchen together with an intelligent assistant to guide patients to relearn meal preparation skills. The intelligent assistant uses fuzzy logic to regulate the visual and audio cues based on the patient's behaviours being monitored. A preliminary clinical trial indicates that the intelligent electronic exercises could complement existing conventional rehabilitation activities in hospitals and enable therapists to better concentrate on the patient's performances and assessment.